2017
DOI: 10.1371/journal.pone.0182911
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of Roundup Full II® on lymphocytes of Chaetophractus villosus (Xenarthra, Mammalia): In vitro studies

Abstract: In Argentina, Chaetophractus villosus has a wide distribution that overlaps with agricultural areas where soybean is the predominant crop. In such areas the pesticide Roundup Full II® (RU) is widely applied. The genotoxic effect of its active ingredient glyphosate (RU is 66.2% glyphosate) on the peripheral blood lymphocytes of C. villosus was tested over a range of concentrations (280, 420, 560, 1120 μmol/L). Culture medium without glyphosate served as negative control, while medium containing mitomycin C serv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 33 publications
(43 reference statements)
2
15
0
Order By: Relevance
“…The effect, however, has erroneously attributed to glyphosate (Cai et al, 2017). Among mammals, significant increases in chromosome aberration (including chromatid breaks) frequencies and sister chromatid exchanges per cell were seen in large hairy armadillo Chaetophractus villosus peripheral blood lymphocytes upon treatment with Roundup Full II R at doses corresponding to glyphosate concentrations of 0.065-0.26 mg/ml, confirming genotoxicity of the formulated glyphosate-based herbicide, evaluated by cellular and genetic biomarkers e.g., the mitotic index, cell proliferation kinetics, as well as frequencies of chromosome aberrations and sister chromatid exchanges (Luaces et al, 2017;Rossi et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 59%
“…The effect, however, has erroneously attributed to glyphosate (Cai et al, 2017). Among mammals, significant increases in chromosome aberration (including chromatid breaks) frequencies and sister chromatid exchanges per cell were seen in large hairy armadillo Chaetophractus villosus peripheral blood lymphocytes upon treatment with Roundup Full II R at doses corresponding to glyphosate concentrations of 0.065-0.26 mg/ml, confirming genotoxicity of the formulated glyphosate-based herbicide, evaluated by cellular and genetic biomarkers e.g., the mitotic index, cell proliferation kinetics, as well as frequencies of chromosome aberrations and sister chromatid exchanges (Luaces et al, 2017;Rossi et al, 2018).…”
Section: Registration Of Glyphosate In the European Unionmentioning
confidence: 59%
“…In this study, and compared to the control group, none of the concentrations of RF used were able to induce an increase in neutrophil migration to the injured site. In contrast, other studies have shown the induction of pro-inflammatory states with exposure to glyphosate-containing compounds [ 71 , 72 ].…”
Section: Discussionmentioning
confidence: 87%
“…In peripheral blood lymphocytes from the armadillo Chaetophractus villosus, exposure to RoundUp V R induced more sister-chromatid exchanges and chromosomal aberrations (mostly chromatid breaks) (Luaces et al 2017). Those authors interpreted these outcomes as a sign of alterations in chromosome replication; this was supported by an observation of a slight reduction in the replication index.…”
Section: Genotoxicity and Oxidative Stressmentioning
confidence: 93%